STUDI PERENCANAAN BISNIS PADA BISNIS JASA - Ali, Faiq Tajib; Noermijati, Noermijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to provide business planning recommendations for the Scootify.Id Garage business in the future to maximize business development. Scootify.Id Garage, is a motorcycle maintenance service provider based in Bogor City that specializes in Coating & Detailing services. By offering innovation in vehicle maintenance, Scootify.Id Garage comes as a solution for motorcycle owners who want their vehicle to look its best. Focusing on quality service, Scootify.Id Garage is pursuing a growing market share in Bogor City and surrounding areas. Through this business plan, Scootify.Id Garage is committed to becoming the first choice in the motorcycle maintenance industry by providing reliable service through Coating services to protect vehicle paint, and Detailing to improve vehicle cleanliness and appearance.